(untitled) - Chandra, Praphul (Amsterdam, 2007)
This book will be among the first to discuss Session Initiation Protocol (SIP), Quality of Service (QoS), and interoperability in connection with Wi-Fi telephony. Security challenges are also presented and solved along these malleable wireless boundaries. In short, this book provides all the information necessary for effective, reliable, crystal clear Wi-Fi telephony service and implementation.
Keywords: Internet telephony,Wireless LANs,Điện thoại Internet,Mạng không dây